A Pragmatic Approach to Rhetorical Technique of "Exaggeration" Based on Grice’s "Cooperative Principle" - Rahmani, Hassan; Mokhtari, Qasem; Jorfi, Mohammad; Ebrahim Anari Bozchlooi; Shahbazi, Mahmoud (Funūn-i adabī, 2024)
Exaggeration is among the most prominent rhetorical techniques that has long been of significant interest to linguists and scholars, specifically under the discipline of Badi (rhetorical embellishment). What is important about this rhetorical technique, like any other rhetorical technique, is the process by which it was created and how it is received and read. This study adopts a descriptive-analytical approach to answer this fundamental question and utilizes Grice's "Cooperative Principle" from pragmatic theory to analyze the structural-semantic process of this rhetorical technique. The results indicate that the creation of the rhetorical technique of exaggeration is fundamentally based on the non-observance of what Grice calls the Maxim of "Quality" because, in the process of creating this technique, the person refuses to provide correct and arguable information to the audience, thus refusing to comply with The Maxim of "Quality". Of course, it should be noted that the failure to comply with the Maxim of Quality in this process was intentional and in some way obvious and recognizable [= Flouting the Quality Maxim] and not with the purpose of deceiving or misleading the audience [= violation the Quality Maxim]. Rather, he does this with the aim of guiding him to "Conversational Implicature".This study can be considered an accurate criterion for distinguishing exaggeration from lying. Keywords: The Science of Rhetoric, Exaggeration, Pragmatics, Grice, Cooperative Principle, the Maxim of Quality, Conversational Implicature. Introduction Badi, the art of eloquence, strives to teach us the method of fine speaking. Despite its value and importance, we observe that the beautiful and captivating visage of this science has long been covered in the dust of antiquity and obsolescence, with little effort made to scientifically explain its subtleties and delicacies. Therefore, the current research aims to utilize contemporary linguistic data to delve into the rhetorical technique of Badi and present a more scientific image of this technique to the audience. The rhetorical technique of "exaggeration" (Mubalaghah) is one of these notable techniques. Given its extensive application in literary and everyday language and its ambiguous proximity to false speech, it deserves to be examined and read more thoroughly than any other rhetorical technique. The crucial aspect of this rhetorical technique, like other techniques, is understanding the process by which it is created and received. Undoubtedly, a scientific response to this question can provide a clear picture of the technique of exaggeration for the modern audience and potentially cleanse this rhetorical technique from the ignominy that has been attributed to it by some linguists for many years. Materials and Methods This research is based on a descriptive-analytical method and has been conducted with reference to library sources. To achieve the intended objectives, we utilized one of the prominent theories in the "Pragmatics" approach called the "Cooperative Principle", and based on it, we analyzed the structural-semantic process of the rhetorical technique of exaggeration. Furthermore, we have endeavored to analyze examples containing this rhetorical technique in both Arabic and Persian languages, based on the model derived from the structural-semantic process of exaggeration, and provide a new perspective on them. Research Findings The study of the rhetorical technique of exaggeration shows that this technique is created and finds meaning within a fully communicative context [speaker®audience]. In the process of creating this technique, the speaker (=A) amplifies or diminishes the specific characteristic of a person or thing beyond its actual reality in the external world and presents it to the audience (=B) (=Norm-Breaking); thus, claiming the utmost possession of that specific characteristic by that person or thing (= intentionality). Discussion of Results and Conclusion By aligning the above content with what Grice proposes under the Cooperative Principle and its four maxims, it can be understood that the creation of the rhetorical technique of exaggeration fundamentally relies on the "Flouting the Quality Maxim". In fact, during the creation process of this rhetorical technique, the speaker (=A) is required to provide information that they know is false or cannot substantiate, thus "Flouting" the Quality Maxim. In doing so, the speaker guides the audience (=B) towards "conversational implicature". This research emphasizes that what happens regarding the non-observance of the "Quality Maxim" in the process of creating the rhetorical technique of exaggeration is a " Flouting" that occurs in a conscious, explicit, and recognizable manner; rather than a "violation" which is non-explicit, unrecognizable, and intended to deceive or mislead the audience. This distinction can be considered a precise criterion for differentiating exaggeration from lying.